2022
DOI: 10.1063/5.0086050
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of a droplet impacting on a smooth flat surface: How liquid viscosity influences the maximum spreading time and spreading ratio

Abstract: Existing energy balance models, which estimate maximum droplet spreading, insufficiently capture the droplet spreading from low to high Weber and Reynolds numbers and contact angles. This is mainly due to the simplified definition of the viscous dissipation term and incomplete modeling of the maximum spreading time. In this particular research, droplet impact onto a smooth sapphire surface is studied for seven glycerol concentrations between 0% and 100%, and 294 data points are acquired using high-speed photog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 53 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…Tian and Chen concluded that the surface tension had a greater impact on β max compared to viscosity, based on experimental data of liquids with viscosities ranging from 0.32 to 1.08 mPa·s. However, by comparing the drop spreading of water (μ = 1.0 mPa·s) and glycerol (μ = 1021.5 mPa·s), Aksoy et al reported that the effect of viscosity on β max could not be neglected. Based on the above results, the importance of the viscosity effect is different for different viscosity ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Tian and Chen concluded that the surface tension had a greater impact on β max compared to viscosity, based on experimental data of liquids with viscosities ranging from 0.32 to 1.08 mPa·s. However, by comparing the drop spreading of water (μ = 1.0 mPa·s) and glycerol (μ = 1021.5 mPa·s), Aksoy et al reported that the effect of viscosity on β max could not be neglected. Based on the above results, the importance of the viscosity effect is different for different viscosity ranges.…”
Section: Resultsmentioning
confidence: 99%
“…The result from the impact of a droplet on a solid substrate can be categorized as spreading, splashing, or bouncing. The specific case arises from the competition between inertia, interfacial tension, and viscous forces. , These can be decomposed into the influence of several parameters: viscosity η, density ρ, surface tension σ, impact speed u 0 , and droplet diameter D 0 . In other words, the splashing threshold is characterized by Weber ( We = ρ D 0 u 0 2 / σ ) and Reynolds ( Re = ρD 0 u 0 /η) numbers incorporating inertia, viscous stress, and surface tension.…”
Section: Nanofluid Droplet Splashingmentioning
confidence: 99%
“…The specific case arises from the competition between inertia, interfacial tension, and viscous forces. 1 , 2 These can be decomposed into the influence of several parameters: viscosity η, density ρ, surface tension σ, impact speed u 0 , and droplet diameter D 0 . In other words, the splashing threshold is characterized by Weber ( ) and Reynolds ( Re = ρD 0 u 0 /η) numbers incorporating inertia, viscous stress, and surface tension.…”
Section: Nanofluid Droplet Splashingmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the droplet jetting time was inversely proportional to the impact velocity but the effect of wettability can be negligible. Aksoy et al (Aksoy, Eneren, Koos, & Vetrano, 2022) examined a droplet impacting a flat surface. They derived the maximum spreading ratio as a function of Weber number and Reynolds number (Re).…”
Section: Introductionmentioning
confidence: 99%